(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Traditionally India’s tax regime relied heavily on indirect taxes. Revenue from indirect taxes was the major source of tax revenue till tax reforms were undertaken during nineties. There were endless taxes in earlier system - few levied by Centre and rest levied by state. To remove this multiplicity of taxes and reducing the burden of the tax payer a simple tax was required and that is Goods and Service Tax (GST). The Goods and Services Tax (GST), implemented on July 1, 2017, is regarded as a major taxation reform till date implemented in India since independence in 1947. GST was planned to be implemented in April 2010, but was postponed due to political issues and conflicting interest of stakeholders. The primary objective behind development of GST is to subsume all sorts of indirect taxes in India like Central Excise Tax, VATSales Tax, Service tax, etc. and implement one taxation system in India. The GST based taxation system brings more transparency in taxation system and increases GDP rate from 1 to 2 and reduces tax theft and corruption in country. The paper highlights the background of the taxation system, the GST concept along with significant working, comparison of Indian GST taxation system rates with other world economies, and also presents in-depth coverage regarding advantages to various sectors of the Indian economy after revising GST and outlines some challenges of GST implementation.